Role of Fetal Doppler and Non-Stress Test in Preeclampsia and Intrauterine Growth Restriction - Yelikar, Kanan A. (Springer India, 2013)
OBJECTIVES: To study the efficacy of fetal Doppler and non-stress test (NST) in predicting fetal compromise in preeclampsia and growth-restricted fetuses. METHODS: ln a prospective study, 189 pregnant women beyond 32 weeks of gestation with preeclampsia or growth-restricted fetuses confirmed by ultrasound were evaluated by Doppler velocimetry (umbilical and middle cerebral artery) and non-stress testing. The outcome of pregnancy was recorded according to Group I (n = 109, Doppler and NST normal), Group II (n = 48, Doppler abnormal and NST normal), Group III (n = 14, Doppler normal and NST abnormal), and Group IV (n = 18, Doppler and NST both abnormal). The evaluation was done by Chi square testing. RESULTS: Both Doppler and NST had a better specificity and negative predictive value, indicating that these tests were more predictive of a healthy fetus. The fetal compromise in terms of APGAR scores, NICU admissions, birth weight, etc., was greater when both Doppler and NST were abnormal. Doppler detected changes earlier in the disease cascade than NST as evidenced by the lead time of 5.86 days. CONCLUSION: The use of both the tests is necessary as it helps in detecting a spectrum of fetuses compromised at various stages of disease affection.